Transactional or Transformational Leadership: Which Works Best for Now? - Umme Salma, Sultana; Mohd Ridzuan, Darun; Liu, Yao (Penerbit Universiti Malaysia Pahang, 2015)
The study of leadership started before ages. We found this study with a variety of academic details and in different framework. With the time culture also changed of an organization, it is now more complicated. Present corporate context requires a more efficient leader with clear vision and motivation power, instead of dominant personality. Transactional and Transformational leadership styles got notable attentions of many researchers from decades. This study explores the distinctiveness of Transactional and Transformational leadership from literature. Various differences have been drawn between these leadership styles to identify which one is more applicable for present corporate context. The paper concludes that both Transactional and Transformational leadership styles have weaknesses and strengths, although Transformational leadership style is more acceptable in present context.